2007
DOI: 10.1007/s00428-007-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of sex steroid hormone receptors in C cell hyperplasia and medullary thyroid carcinoma

Abstract: Previous studies have shown that C cells are twice as numerous in male than in female thyroids and that C cell hyperplasia (CCH) is much more frequent in men. These findings suggest regulation involving sex steroid hormones through the expression of sex steroid hormone receptors on C cells. To investigate this hypothesis, we performed an immunohistochemical study of estrogen receptors alpha (ER alpha) and beta (ER beta), progesterone receptors (PR), and androgen receptors (AR) on specimens from a series of 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Receptors for both androgens and estrogens were detected in these cells [34][35][36], and we have shown that estrogen had a positive effect on the secretory activity of thyroid C cells [37]. Reporter gene assays of nuclear hormone receptor activity with phytochemicals suggested that daidzein preferentially interacts with ERβ but does not show androgen receptor activity [38].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Receptors for both androgens and estrogens were detected in these cells [34][35][36], and we have shown that estrogen had a positive effect on the secretory activity of thyroid C cells [37]. Reporter gene assays of nuclear hormone receptor activity with phytochemicals suggested that daidzein preferentially interacts with ERβ but does not show androgen receptor activity [38].…”
Section: Discussionmentioning
confidence: 89%
“…Reporter gene assays of nuclear hormone receptor activity with phytochemicals suggested that daidzein preferentially interacts with ERβ but does not show androgen receptor activity [38]. Based on these recent studies, we can suggest that daidzein may predominantly act on thyroid C cells by binding to ERβ, which are detected in them [35]. However, at this level and without experiment, AR/ER blockade, is not possible to give a definite answer about whether daidzein affects C cells as an estrogen or androgen receptor agonist, and this answer should be provided by future research.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of mRNA for ERα and ERβ has also been demonstrated in human MTC tumour tissues [92]. In a study by Blechet et al [93], ERβ was expressed in CCH in 100% and in MTC 96.5% of cases whereas ERα was never expressed. Thus, the hypothetical role of ER subtypes in human MTC remains to be established.…”
Section: Molecular Biology Of Mtc and The Ret Proto-oncogenementioning
confidence: 99%
“…Previously, ERb expression has been reported in normal thyroid parafollicular C cells (Taylor & Al-Azzawi 2000) and MTC tumor tissues (Blechet et al 2007). The presence of mRNA for ERa and ERb has also been demonstrated in the human MTC tumor tissues (Egawa et al 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Immunohistochemical studies using monoclonal antibody revealed that ERb, but not ERa, was detected in normal human thyroid follicular and parafollicular C cells (Taylor & Al-Azzawi 2000). More recently, a study showed that ERb was expressed in most of the MTC tissues (Blechet et al 2007). However, immunohistochemistry results (Bur et al 1993, Colomer et al 1996, Lewy-Trenda 2002, Arain et al 2003, Blechet et al 2007 demonstrating ERa expression in thyroid tumors including follicular adenoma or carcinoma, papillary carcinoma, medullary carcinoma, and anaplastic carcinoma remain controversial depending on the antibody source.…”
Section: Introductionmentioning
confidence: 99%